Long-term resource addition to a detrital food web yields a pattern of responses more complex than pervasive bottom-up control - Lawrence, Kendra L.; Wise, David H. (PeerJ, 2017)
Background Theory predicts strong bottom-up control in detritus-based food webs, yet field experiments with detritus-based terrestrial systems have uncovered contradictory evidence regarding the strength and pervasiveness of bottom-up control processes. Two factors likely leading to contradictory results are experiment duration, which influences exposure to temporal variation in abiotic factors such as rainfall and affects the likelihood of detecting approach to a new equilibrium; and openness of the experimental units to immigration and emigration. To investigate the contribution of these two factors, we conducted a long-term experiment with open and fenced plots in the forest that was the site of an earlier, short-term experiment (3.5 months) with open plots (Chen & Wise, 1999) that produced evidence of strong bottom-up control for 14 taxonomic groupings of primary consumers of fungi and detritus (microbi-detritivores) and their predators. Methods We added artificial high-quality detritus to ten 2 × 2-m forest-floor plots at bi-weekly intervals from April through September in three consecutive years (Supplemented treatment). Ten comparable Ambient plots were controls. Half of the Supplemented and Ambient plots were enclosed by metal fencing. Results Arthropod community structure (based upon 18 response variables) diverged over time between Supplemented and Ambient treatments, with no effect of Fencing on the multivariate response pattern. Fencing possibly influenced only ca. 30% of the subsequent univariate analyses. Multi- and univariate analyses revealed bottom-up control during Year 1 of some, but not all, microbi-detritivores and predators. During the following two years the pattern of responses became more complex than that observed by Chen & Wise (1999). Some taxa showed consistent bottom-up control whereas others did not. Variation across years could not be explained completely by differences in rainfall because some taxa exhibited negative, not positive, responses to detrital supplementation. Discussion Our 3-year experiment did not confirm the conclusion of strong, pervasive bottom-up control of both microbi-detritivores and predators reported by Chen & Wise (1999). Our longer-term experiment revealed a more complex pattern of responses, a pattern much closer to the range of outcomes reported in the literature for many short-term experiments. Much of the variation in responses across studies likely reflects variation in abiotic and biotic factors and the quality of added detritus. Nevertheless, it is also possible that long-term resource enhancement can drive a community towards a new equilibrium state that differs from what would have been predicted from the initial short-term responses exhibited by primary and secondary consumers.
Keywords: Leaf litter; Arthropod community; Field experiment; Control processes; Detritus; Long-term; Collembola; Araneae; Pseudoscorpiones; Coleoptera